DEVELOPMENT OF ETHNOMATHEMATICS-BASED E-MODULE FROM DUKUTAN TRADITION OF KARANGANYAR COMMUNITY TO IMPROVE STUDENTS' MATHEMATICS LEARNING OUTCOMES ON LINEAR EQUATIONS AND INEQUALITIES - Henny Ekana Chrisnawati (Universitas Sebelas Maret, 2024)
This study is motivated by the lack of comprehensive mathematics learning resources. At times, teachers open instructional videos, then books, and browse websites, which inevitably leads students to rely on scattered learning sources. So, this research aims to develop a realistic mathematics education (RME)-based mathematics e- module integrated with the ethnomathematics of the Dukutan Tradition, which is a tradition in Karanganyar Regency on the material of the Linear Equation and Inequality System for Wikarya Karanganyar Vocational High School, to determine the level of validity of the developed mathematics e-module and to find out the user's response to the developed e-module, and measure the effectiveness of the e-module in terms of student learning outcomes. The development model used in this research is the ADDIE model with the stages of Analysis, Design, Development, Implementation, and Evaluation. The subjects of this study were class X Office Management and Business Services students of Wikarya Karanganyar Vocational High School, totaling 26 students in the 2023/2024 academic year. Data were collected using tests, observations, questionnaires, and documentation. The results of the study are (1) the average score obtained from the validation of material, media, and cultural experts is 0,895 which is included in the high validity category (2) the average score of teacher responses with a percentage of 89,5% which is included in the very practical category (3) the average score of student responses with a percentage of 92,75% which is included in the very practical category (4) the N-Gain average is 0,73 or in the form of a percentage of 73% which is included in the high improvement category with the level of effectiveness in the moderately effective category. Based on the results of the study, it can be concluded that the mathematics e-module developed by the researcher is included in the valid, practical, and effective mathematics e-module to improve student learning outcomes so that it is suitable for use to increase understanding of the concept of Linear Equation and Inequality System material for grade X students. Keywords: E-Modules, Realistic Mathematic Education (RME), Dukutan Tradition Ethnomathematics, Linear Equation And Inequality System, Student Learning Outcomes